Is vaccine hesitancy related to mental health after the adjustment of the zero-COVID-19 strategy in the elderly? A mediation analysis in China - Enming Zhang; Xiaolong Wang; Zhengyue Dai; Xian Zhang; Shuhui Shang; Qiong Fang (Human Vaccines & Immunotherapeutics)
With the global Omicron pandemic and the adjustment of the zero-coronavirus disease 2019 (zero-COVID-19) strategy in China, there is a critical need to improve vaccination rates among older adults while addressing the mental health issues associated with vaccination. This study investigated levels of COVID-19-related anxiety, depression, benefit finding, and fear in older adults and explored the relationship between vaccine hesitancy, sociodemographic factors, and mental health. Participants aged 60 and older (n = 658) were recruited from several cities in the eastern, central, and western China regions. Of these, 347 exhibited vaccine hesitancy. The effects of residence, education, health status, and COVID-19 vaccination on anxiety/depression/benefit-finding were found to be mediated/suppressed by vaccine hesitancy. Additionally, in investigating psychological antecedents, older people without vaccine hesitancy showed higher confidence, lower complacency, fewer constraints, and a greater sense of collective responsibility. This study advances our understanding of mental health differences in anxiety, depression, and benefit-finding across sociodemographic characteristics. It is essential to improve population confidence related to vaccines, accessibility to vaccination services, and responsibility to mitigate vaccine hesitancy while paying close attention to the mental health associated with vaccination in older adults.